PREMIUM PRICING IN HEALTH INSURANCE BY NELSON- AALEN ESTIMATOR - Najmah Istikaanah (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2011)
In this paper the using of Nelson Aalen estimators are presented to estimate transition probabilities of multistate model. Based on discrete time Markov, we will get transition matrices?é?á which the elements are transition probabilities from Nelson Aalen estimator. Because of the data that used in the construction of transition matrices are person?óÔé¼Ôäós health histories, then it can be seen as a morbidity value, which can be used to premium pricing.?é?á Key words: Markov process, multistate model, Nelson Aalen, transition probability.